Word Of Mouth Marketing Dalam Konsep Pemasaran Syari’ah Terhadap Keputusan Pembelian Di Albariqi Bistro Tanjungpinang - Kamaruzaman Kamaruzaman; Nufikha (EMASHA: Jurnal Ekonomi, Manajemen dan Akuntansi Syariah, 2024)
This research aims to determine the influence of word of mouth in the sharia marketing concept on purchasing decisions at Albariqi Bistro Tanjungpinang, Riau Islands Province. The population of this research was Albariqi Bistro Tanjungpinang consumers, 640 respondents with a total sample of 86 respondents. Data collection was carried out using the questionnaire method. The analysis technique using SPSS Version 26 includes instrument analysis in the form of validity and reliability analysis. The results of the validity analysis showed that all 15 statement items were proven to be valid, while the results of the reliability analysis showed a reliability coefficient of 0.968, so they were declared reliable. Data analysis includes classical assumption tests and simple regression tests. The results of the classical assumption test research showed that the normality test was normally distributed and the heteroscedasticity test did not detect heteroscedasticity. The results of the simple regression test research show that the coefficient of determination (R Square) is 0.752 or 75.2%. The t test shows that the results of tcount are 15.939 and ttable 1.988 with a significance value of 0.000 <0.05. The F test shows that the Fcount = 254.039 with a significance value of 0.000 <0.05, so it can be concluded that there is an influence of the word of mouth variable on the purchasing decision variable.